Distress thermometer for preoperative screening of patients with oral squamous cell carcinoma. Issue 7 (July 2018) - Schell, Juliana-Theresa; Petermann-Meyer, Andrea; Kloss-Brandstätter, Anita; Bartella, Alexander K.; Kamal, Mohammad; Hölzle, Frank; Lethaus, Bernd; Teichmann, Jan
Abstract: In this study, we evaluate the association between distress, various demographic and medical variables, and the prevalence of psychosocial distress in preoperative patients with oral squamous cell carcinoma. A total of 100 consecutive patients were recruited into the study and asked to complete the Distress Thermometer (DT) form with the Problem List questionnaire prior to surgical intervention; the average distress score was 5.7 ± 2.7. The distress score was neither correlated with age (r = −0.025; p = 0.804) nor with tumor size (r = 0.028; p = 0.785). General worries, anxiety, sadness, depression, pain, exhaustion, sleeping disorders, or problems with nutrition resulted in significantly higher distress scores compared to patients without these complaints. Individuals with a DT score of 5 or higher (p = 0.006) were advised to seek out psychological support. There is a strong correlation between a high DT score and emotional disorders, as well as physical problems.